Inheritance Pattern and Cross-Resistance Assessment of Flonicamid Resistance in the Biological Control Agent Chrysoperla carnea (Neuroptera: Chrysopidae) - Khan, Arbaz; Sarfraz Ali Shad (Jurusan Budidaya Perkebunan, 2025)
A field-collected laboratory population of Chrysoperla carnea, a polyphagous predator important in integrated pest management, was subjected to flonicamid selection pressure for three generations using a micro-droplet topical bioassay. Following selection, the flonicamid-selected strain exhibited 6.83-fold resistance (LC50 = 260,730 ppm; 95% FL = 148,090–1,561,600 ppm) compared with the unselected strain (LC50 = 38,122 ppm; 95% FL = 23,259–138,440 ppm). Reciprocal crosses between resistant and susceptible parents produced overlapping 95% FLs, demonstrating autosomal inheritance with no detectable maternal or sex-linked effects. Dominance metrics indicated incomplete to partial dominance of resistance (DLC = 0.60 for F1; DLC = 0.55 for F2). Effective dominance estimates at four diagnostic doses (27,875; 62,500; 125,000; 272,000 ppm) yielded ED values of 0.53, 0.79, 0.91, and 0.88, respectively, showing increased dominance at higher doses. Chi-square goodness-of-fit tests rejected the null hypothesis of monogenic inheritance (p < 0.05), confirming a polygenic resistance model. Cross-resistance bioassays further revealed substantial co-selection effects, with resistance ratios of 24.35-fold for acetamiprid, 23.58-fold for triazophos, and 15.17-fold for deltamethrin, comparing initial and final LC50 values that showed non-overlapping 95% FLs. These results indicate that flonicamid resistance in C. carnea is a polygenic, autosomal, and incompletely to partially dominant trait. The findings provide genetic foresight for incorporating resistant predator populations into insecticide-compatible IPM programs and highlight the importance of mode-of-action-based chemical rotation to mitigate resistance co-selection in beneficial predator populations.